Energy Performance of CHP System Integrated with Citrus Peel Air-Steam Gasification: a Comparative Study. (September 2017) - Galvagno, A.; Prestipino, M.; Chiodo, V.; Maisano, S.; Brusca, S.; Lanzafame, R.
Abstract: The aim of this work is to exploit the potential of residual biomass, different from the traditional wood feedstock, by thermochemical gasification process. In particular, citrus peels waste of the juice extraction process, was selected since it is a typical local Sicilian residue. The citrus peel conversion performances in air-steam gasification process were evaluated and compared with those obtained with pinewood as feedstock. Experimental activities of air-steam gasification were carried out in a bench-scale fluidized bed reactor at 1023 K, for both citrus peel and pinewood, varying the steam to biomass ratio (S/B). A simulation model of the experimental facility was developed in order to find a useful tool to realize the virtual scale-up of the system with downstream syngas utilization. The cold gas efficiency (CGE) and the net cold gas efficiency (CGEnet ) were calculated to define the best gasification conditions. Results showed that using pinewood a very low reactivity can be observed, showing a very low net CGE. The highest net CGE for citrus peel was observed at S/B = 0.5, while for pinewood the addition of water did not improve the net CGE. Finally, an integration of the citrus peel gasification system with a commercial CHP unit was proposed and the efficiencies were evaluated.